Preparation of vacuum deposited cadmium selenide thin films for optoelectronic applications. (2016) - Santhosh, T.C.M.; Bangera, Kasturi V.; Shivakumar, G.K.
Abstract: Cadmium selenide is a direct band gap material which finds applications in optoelectronic devices. Preparation of the compound semiconductor in thin film form with stable electrical characterization has been investigated in the present study. As deposited films at room temperature (25°C) are non-stoichiometric with excess cadmium and films grown at 180°C substrate temperature are stoichiometric and homogeneous. The crystallinity increases with increase in substrate temperature. The optical band gap determined from absorption measurements lie in the range 1.89 eV – 2.02 eV. Electrical conductivity measurements made in a temperature range from 25°C to 200°C yield thermal activation energy of 0.52eV for stoichiometric films. Films deposited at 180° C and annealed at 200° C for two hours are found to be stabilized in its electrical and structural properties.